Penerapan Strategi Membaca Bergema untuk Meningkatkan Kelancaran Membaca Siswa Kelas II Sekolah Dasar Negeri Labuy Aceh Besar - Afisha, Amna; Jarmita, Nida (Pencerah, 2025)
Based on preliminary observations conducted by the researchers on second-grade students at Labuy State Elementary School, it was found that the students' reading skills were still suboptimal. This was evidenced by frequent errors made during reading activities in Indonesian language lessons, preventing many students from meeting the expected reading fluency standards. Out of 24 students, only 10 met the minimum competency criteria, while the remaining 14 did not. To address this issue, a reverberating reading strategy supported by leveled books was implemented to enhance reading fluency. The aim of this study was to improve students’ reading fluency through the use of a reverberating reading strategy assisted by leveled books. The research employed a Classroom Action Research (CAR) approach involving 24 second-grade students. Data were collected through observations and tests. The data analysis revealed that teacher activity improved from 76.04% in Cycle I to 92.7% in Cycle II, while student activity increased from 72.91% to 95.83% over the same period. Similarly, students' reading fluency improved from 62.50% in Cycle I to 87.50% in Cycle II. The results of the study indicate that the echo reading strategy has a positive effect on students’ reading fluency. By imitating the way the teacher reads, including pronunciation, intonation, and pauses, students are able to pronounce words more accurately, read more smoothly, and develop proper intonation. The echo reading strategy has been proven effective in improving students’ reading fluency, especially for lower-grade students who still require direct guidance. By imitating the teacher’s reading, students gain concrete examples of correct reading, and their oral reading skills develop gradually. Teachers are encouraged to apply the echo reading strategy regularly and provide continuous guidance to ensure that students’ reading fluency can improve optimally.